The insight of in vitro and in silico studies on cholinesterase inhibitors from the roots of Cimicifuga dahurica (Turcz.) Maxim. - Jang Hoon Kim; Nguyen Phuong Thao; Yoo Kyong Han; Young Suk Lee; Bui Thi Thuy Luyen; Ha Van Oanh; Young Ho Kim; Seo Young Yang (Taylor & Francis Group, 2018)
Cholinesterases (ChEs) are enzymes that break down neurotransmitters associated with cognitive function and memory. We isolated cinnamic acids (1 and 2), indolinones (3 and 4), and cycloartane triterpenoid derivatives (5-19) from the roots of Cimicifuga dahurica (Turcz.) Maxim. by chromatography. These compounds were evaluated for their inhibitory activity toward ChEs. Compound 1 was determined to have an IC50 value of 16.7 ± 1.9 μM, and to act as a competitive inhibitor of acetylcholinesterase (AChE). Compounds 3, 4 and 14 were found to be noncompetitive with IC50 values of 13.8 ± 1.5 and 6.5 ± 2.5 μM, and competitive with an IC50 value of 22.6 ± 0.4 μM, respectively, against butyrylcholinesterase (BuChE). Our molecular simulation suggested each key amino acid, Tyr337 of AChE and Asn228 of BuChE, which were corresponded with potential inhibitors 1, and 3 and 4, respectively. Compounds 1 and 4 were revealed to be promising compounds for inhibition of AChEs and BuChEs, respectively.